Automorphisms and isomorphisms of quantum generalized Weyl algebras - Suárez-Alvarez, Mariano (2015)
We classify up to isomorphism the quantum generalized Weyl algebras and determine their automorphism groups in all cases in a uniform way, including the case where the parameter q is a root of unity, thereby completing the results obtained by Bavula and Jordan (2001) [5] and Richard and Solotar (2006) [12].